2021
DOI: 10.1002/jcu.22996
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chest conformation on ventricular‐arterial coupling during normal pregnancy

Abstract: Purpose There is still controversy regarding the changes of ventricular‐arterial coupling (VAC) during normal pregnancy. The possible influence of chest shape on VAC during normal pregnancy has never been investigated. Methods Between October 2019 and June 2020, 59 healthy pregnant women (33.7 ± 4.4 years/old) were consecutively included. They underwent obstetric visit, modified Haller index (MHI) assessment, and complete echocardiographic evaluation with blood pressure measurement to assess arterial elastance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…MHI has been developed in our echo lab in the last decade and has been validated in 2018 13 . In the last few years, we have employed this non‐radiological method to assess the possible influence of a concave‐shaped chest wall on cardiac kinetics and function in different clinical settings 12,28–33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MHI has been developed in our echo lab in the last decade and has been validated in 2018 13 . In the last few years, we have employed this non‐radiological method to assess the possible influence of a concave‐shaped chest wall on cardiac kinetics and function in different clinical settings 12,28–33 …”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, which were mostly conducted in middle‐aged healthy adults, we demonstrated that the anterior chest wall deformity is a decisive factor in determining an impairment of myocardial strain parameters in different patient populations, 12,28,29 in influencing stroke volume and ventricular‐arterial coupling (VAC) parameters in healthy pregnant women 30 and finally in affecting stress echocardiographic results and outcome 31–33 . The impairment in 2D‐STE derived myocardial strain indices, the modification in VAC parameters and the exercise‐induced left ventricular regional wall motion abnormalities were all strongly associated to MHI, in absence of any intrinsic myocardial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The Italian study that involved 16 infants with pes excavatum and 44 infants with normal chest shape revealed significantly deteriorated values of left and right ventricular mechanics in infants with chest abnormality in comparison with controls. 3 The authors revealed that abnormal chest anatomy progressively deteriorated myocardial strain parameters in infants with pes excavatum and this impairment is probably the consequence of intraventricular dyssynchrony due to compressive phenomena than intrinsic myocardial dysfunction.…”
mentioning
confidence: 99%